Taxonomia integrativa da subfamília Aphyocharacinae (Teleostei: Characidae) da região hidrográfica atlântico nordeste ocidental e drenagens adjacentes - BRITO, Pâmella Silva de (2021)
Aphyocharacinae is a monophyletic subfamily within Characidae, including a total of 23 valid species. It was originally proposed by Eigenmann (1909) to include the genera Coelurichthys (=Mimagoniates), Odontostilbe, Holoshesthes (=Odontostilbe), Cheirodon and Aphyocharax, which comprised fishes possessing a single series of well-developed teeth in the premaxilla, dentary and maxilla. Since that, Aphyocharacinae has been successively considered valid, or even your genera were included in the subfamilies Cheirodontinae and Characinae. The initial history of Aphyocharacinae is confused, with many taxonomic misunderstandings and errors, such as: descriptions of incorrect or unclear species, incongruence of name priority among subfamilies, some of them persisting to the present days. Thus, one way of overcoming the confusing taxonomy of problematic groups, having accuracy in species identification and diversity estimates of species groups is using different and independent operational criteria for species delimitation. Therefore, the aim of this project is to carry out a integrative taxonomic study among species and populations within the subfamily Aphyocharacinae, occurring in the river basins of the Atlântico nordeste ocidental and adjacent drainages region, based on different and independent methods of species delimitation, and to make taxonomic decisions the basis of these methods.